2018
DOI: 10.4236/jtr.2018.64024
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Sago-Like Nodules on Gross Thoracoscopic Appearance in Tuberculous Pleural Effusion and Their Correlation with Final Histo-Microbiologic Findings

Abstract: Background: Distinguishing tuberculous pleural effusion (TPE) from other causes of exudative effusion is often challenging. Delay in treatment initiation can occur while awaiting histo-microbiologic confirmation owing to the paucibacillary nature of the disease. Sago-like nodules are the most common visual finding on gross thoracoscopic appearance. The primary objective was to determine the diagnostic utility of the presence of sago-like nodules on gross thoracoscopic appearance in TPE to help justify early in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…The sensitivity, specificity and positive predictive value of sago nodules was 58.9 %, 92.6 % and 94.29 % respectively. This is in concordance with the results of Thomas et al, where they reported sensitivity, specificity and positive predictive value of sago nodules for tuberculous pleural effusion to be 58 %, 89 % and 97 % respectively 22 . This also agrees with the results from a Chinese study which reported a sensitivity, specificity and positive predictive value of miliary nodules on pleural as 64.47 %, 86.67 % and 96.08 % respectively 23 .…”
Section: Discussionsupporting
confidence: 92%
“…The sensitivity, specificity and positive predictive value of sago nodules was 58.9 %, 92.6 % and 94.29 % respectively. This is in concordance with the results of Thomas et al, where they reported sensitivity, specificity and positive predictive value of sago nodules for tuberculous pleural effusion to be 58 %, 89 % and 97 % respectively 22 . This also agrees with the results from a Chinese study which reported a sensitivity, specificity and positive predictive value of miliary nodules on pleural as 64.47 %, 86.67 % and 96.08 % respectively 23 .…”
Section: Discussionsupporting
confidence: 92%
“…“Sago”‐like nodules are the most common visual appearance, and its presence has high specificity and positive predictive value to make a diagnosis of tubercular pleural effusion 1 . In the index case, thoracoscopic biopsy revealed multiple aggregates of epitheloid cell granulomas with multinucleated giant cells, caseous necrosis (Figure 2A), and multiple acid fast bacilli on Zeihl Neelsen stain (Figure 2B) confirming the diagnosis of tuberculosis.…”
Section: Discussionmentioning
confidence: 94%
“…This contradicts previous literature which suggests that the presence of nodules is pathognomonic of malignant disease [7]. Nodules have been described in benign diseases such as tuberculosis (sago pattern) [18] and rarely rheumatoid nodules have been described [19]. There are benign lesions that mimic a localized nodule such as thoracic splenosis, pleural endometriosis, thoracolithiasis, foreign bodies, pleural plaques, and pleural pseudotumor [20].…”
Section: Discussionmentioning
confidence: 97%